TEACHING VOCABULARY BY USING REALIA (REAL-OBJECT) MEDIA - Dodi Irawan (Program Studi Pendidikan Bahasa Inggris, 2017)
English is one of scary subject for some students of Indonesia. The students feel afraid to speak in English because of their less word of vocabulary. Realia media is the one simple interesting media that may bring motivation for the student who afraid to study English. Teacher of English can use realia media and bring it in the class to get more attention, and participation of students. In this research, the writer try to focuses on how realia media make significant difference ability of vocabulary to the students. The reserach of this study used a quasi-experimental method the population of this research was taken from the seventh grade Students of SMP Negeri 23 Palembang in the academic of year 2015/2016. Based on the research, it found that there was a significance difference using Realia media in teaching vocabulary. From the result on this research, it was found that there is a significant difference in achievement before and after the treatment in experimental group.